2018
DOI: 10.3389/fncel.2018.00259
|View full text |Cite
|
Sign up to set email alerts
|

Counter-Balance Between Gli3 and miR-7 Is Required for Proper Morphogenesis and Size Control of the Mouse Brain

Abstract: Brain morphogenesis requires precise regulation of multiple genes to control specification of distinct neural progenitors (NPs) and neuronal production. Dysregulation of these genes results in severe brain malformation such as macrocephaly and microcephaly. Despite studies of the effect of individual pathogenic genes, the counter-balance between multiple factors in controlling brain size remains unclear. Here we show that cortical deletion of Gli3 results in enlarged brain and folding structures in the cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…A recent study showed that TBX5 regulates the SALL4 gene and interacts with the SALL4 protein to regulate heart and upper limb development and establish thumb morphogenesis. Pathogenic SALL4 and TBX5 variants cause autosomal dominant Duane-radial ray syndrome (DRRS; also known as Okihiro syndrome) [ 31 , 32 ] and Holt-Oram syndrome (HOS) [ 33 ].…”
Section: Role Of Sall4 In the Morphogenesis Of The...mentioning
confidence: 99%
“…A recent study showed that TBX5 regulates the SALL4 gene and interacts with the SALL4 protein to regulate heart and upper limb development and establish thumb morphogenesis. Pathogenic SALL4 and TBX5 variants cause autosomal dominant Duane-radial ray syndrome (DRRS; also known as Okihiro syndrome) [ 31 , 32 ] and Holt-Oram syndrome (HOS) [ 33 ].…”
Section: Role Of Sall4 In the Morphogenesis Of The...mentioning
confidence: 99%
“…Interestingly, miR-7 has been shown to inhibit Pax6 protein expression without altering its mRNA levels (Needhamsen et al, 2014;Zhang et al, 2018). Moreover, the 3'UTR of Pax6 bears a functional miR-7 target site only in primates, suggesting that this interaction emerged during evolution linked to brain expansion (Needhamsen et al, 2014).…”
Section: Post-transcriptional Influence Of Mir3607mentioning
confidence: 99%
“…As the primary source of mature MiR7, MiR7a shows broad expression in the cortical plate and ventricular zone of embryonic brains ( 40 ). Simultaneous suppression of MiR7 precursors causes dysregulated expression of critical transcription factors including TP53 and PAX6, and consequentially results in defective neurogenesis and microcephaly-like brain defects at birth ( 40, 41 ). Meanwhile, an in vitro study reported that intrinsically programmed downregulation of MiR7 in oligodendrocyte precursor cells (OPCs) is important for proper fate transition of OPCs into mature oligodendrocytes (OLs), which generate insulating myelin sheath surrounding neuronal axons to facilitate fast electrical conduction ( 42 ).…”
Section: Introductionmentioning
confidence: 99%